W poszukiwaniu siebie… Młodzież na drodze do samorealizacji - Słupska, Kamila (Kultura-Społeczeństwo-Edukacja, 2016)
The article raises the issue of the young generation’s striving for the realisation of its potential and talents as well as the use of development opportunities in the context of both favourable and unfavourable conditions of the social-cultural reality. The problems resulting from the axionormative chaos, differentiated opportunities, and changes in all of the areas of life that the contemporary youth wanting to appear on the societal arena is struggling with are also indicated in the article. The considerations oscillate around the categories of identity, needs, existential dilemmas and self-improvement as well as the goals and life plans of young people.